THE EFFECT OF ACID ETCHING TREATMENT ON SURFACE PROPERTIES OF DENTAL HARD TISSUE - Maria Iancu; Norina Forna; Aurora Antoniac; Marius Manole; Octavian Trante; Paltanea Veronica; Doriana Forna; Gabriela Cioca; Nicolcescu Pantelie (Romanian Journal of Oral Rehabilitation)
Our study aims to investigate the acid etching treatment effects applied on dental structures, considering their surface properties. We have used a liquid PA in a concentration of 36.1% wt. (36.1% PA) and a gel PA with 35% wt. (35% PA) active compound as etching agents. These substances were applied to the human teeth for a maximum of 15 seconds. As investigation methods, the surface roughness was determined based on atomic force microscopy (AFM), and we analyzed the surface morphology in detail using scanning electron microscopy (SEM). Then, we analyzed the hydrophile character of the dental structure by experimentally measuring the contact angle (CA) and computed the surface energy (SFE). Following this study, we can say that both investigated etching treatments produce the demineralization of both enamel and dentine structures, with a higher degree in the case of liquid PA (36.1%). Increasing the values for the surface free energy will favor better infiltration and polymerization of the bonding systems.